2020
DOI: 10.3389/fevo.2020.00268
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Diversity and Metabolic Profiles of Bacterial Communities Associated With Antarctic Sponges (Terra Nova Bay, Ross Sea)

Abstract: Complex cell-to-cell interactions (including the production of antibiotics and the quorum sensing phenomenon) occur between benthic marine organisms and bacteria, leading to the establishment of synergistic interactions, especially in extreme and harsh environments, such as Antarctica. Despite this, current data concerning the composition, host-and site-relatedness, and biotechnological values of the bacterial community associated with Antarctic sponges are limited to few works, resulting in a still fragmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 59 publications
4
14
0
Order By: Relevance
“…Less abundant members living within H. pilosus and H. ( Rhizoniera ) dancoi belonged to the classes Nitrospinia (phylum Nitrospinae) and Nitrosophaeria (phylum Thaumarchaeota) ( Figure 2 ; Tables S6 and S7 ). Recent investigations already reported low percentages of Nitrospinia from H. pilosus , H. ( Rhizoniera ) dancoi and other Antarctic species [ 26 , 29 ]. Concerning the capability to produce molecules with biotechnological potential, very little information is available so far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Less abundant members living within H. pilosus and H. ( Rhizoniera ) dancoi belonged to the classes Nitrospinia (phylum Nitrospinae) and Nitrosophaeria (phylum Thaumarchaeota) ( Figure 2 ; Tables S6 and S7 ). Recent investigations already reported low percentages of Nitrospinia from H. pilosus , H. ( Rhizoniera ) dancoi and other Antarctic species [ 26 , 29 ]. Concerning the capability to produce molecules with biotechnological potential, very little information is available so far.…”
Section: Discussionmentioning
confidence: 99%
“…Although a good knowledge is available on sponge fauna, the Antarctic region covers an extraordinarily wide area that makes some zones almost unknown to the scientific community [ 20 , 21 ]. Until now, a few studies have investigated the composition of microbial communities living within Antarctic sponges [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Some of these studies have demonstrated that Antarctic sponges are mostly dominated by Proteobacteria and Bacteroidetes [ 23 , 26 , 29 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sponge Mycale ( Oxymycale ) acerata ( Kirkpatrick, 1908 ) is one of the most dominant members of shallow-water Antarctic benthos ( Cerrano et al, 1974 ; McClintock et al, 2005 ; Cárdenas et al, 2016 , 2018a ); however, while several studies have focused on different aspects of this species ( Cerrano et al, 1974 ; Dayton et al, 1974 ; Riesgo et al, 2015 ; Morley et al, 2016 ), there is still limited information on the microbial communities associated with this ecologically important species. Current knowledge about microbial communities associated with M. acerata is limited to a few specimens from East Antarctica ( Webster et al, 2004 ) and the Ross Sea Region ( Papale et al, 2020 ; Ruocco et al, 2021 ), while information on M. acerata from the Western Antarctic Peninsula (WAP) is also limited to some samples from King George Island, Doumer Island ( Cárdenas et al, 2018a , 2019 ), and Deception Island ( Sacristán-Soriano et al, 2020 ). Results from these studies show the existence of diverse microbial communities, dominated by a few OTUs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have applied such approach to investigate the Antarctic sponge-associated communities and to predict their functional role. Both Steinert et al [197] and Papale et al [198] studied the bacterial communities associated with Antarctic sponges (from two different areas) by carrying out a predictive analysis on metagenome. The authors detected a possible involvement of associated bacteria in xenobiotic biodegradation and secondary metabolites biosynthesis.…”
Section: Methodological Approach On Polar Environments For Bioprospecmentioning
confidence: 99%